2015
DOI: 10.1002/jemt.22608
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence microscopy study on the cytoskeletal displacements during sperm differentiation in the bush‐cricket Tylopsis liliifolia (Fabricius) (Orthoptera: Tettigoniidae)

Abstract: A study by fluorescence microscopy has been carried out on male gametes from testicular follicles, seminal vesicles, spermatophores, and seminal receptacles of the bush-cricket Tylopsis liliifolia, focusing the attention on localization and movements of F-actin and α-tubulin during sperm differentiation, since data in this respect are lacking in the Orthoptera. F-actin and α-tubulin positivity was detected in the testicular follicles, in particular at the bridges connecting spermatids of a same clone and aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Spermatogenesis is a differentiation process with the end goal of functional sperm production, involving marked alterations in genetics, cell functions, and chromatin (Lena et al, 2016; Renata et al, 2016) Modification of sperm proteins by sumoylation, including those found in the mid piece, neck, head, and acrosomal region, therefore, could be important for many aspects of sperm function.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogenesis is a differentiation process with the end goal of functional sperm production, involving marked alterations in genetics, cell functions, and chromatin (Lena et al, 2016; Renata et al, 2016) Modification of sperm proteins by sumoylation, including those found in the mid piece, neck, head, and acrosomal region, therefore, could be important for many aspects of sperm function.…”
Section: Discussionmentioning
confidence: 99%